2013
DOI: 10.1128/aem.02520-12
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Anammox, Denitrification, and Codenitrification in Agricultural Soils

Abstract: dAnammox and denitrification mediated by bacteria are known to be the major microbial processes converting fixed N to N 2 gas in various ecosystems. Codenitrification and denitrification by fungi are additional pathways producing N 2 in soils. However, fungal codenitrification and denitrification have not been well investigated in agricultural soils. To evaluate bacterial and fungal processes contributing to N 2 production, molecular and 15 N isotope analyses were conducted with soil samples collected at six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 51 publications
10
112
2
1
Order By: Relevance
“…Finally, co-denitrification may be an additional pathway for N 2 production in sediments. Co-denitrification can generate 29 N 2 by reducing 45 N 2 O, which is produced by using 14 NH 4 + and 15 NO 3 − / 15 NO 2 − in 15 N isotope pairing experiments (Long et al 2013). Nevertheless, the ubiquitous detection of anammox bacteria indicated that anammox must play an important role in N 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, co-denitrification may be an additional pathway for N 2 production in sediments. Co-denitrification can generate 29 N 2 by reducing 45 N 2 O, which is produced by using 14 NH 4 + and 15 NO 3 − / 15 NO 2 − in 15 N isotope pairing experiments (Long et al 2013). Nevertheless, the ubiquitous detection of anammox bacteria indicated that anammox must play an important role in N 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the in situ ferrihydrite enrichments, the NO 3 − and NO 2 − concentrations were decreased (1.5−6.7 μmol L −1 for NO 3 − and 30−32 μmol L −1 for NO 2 − ) in the AQDS amendment but increased (1−15 μmol L −1 for NO 3 − and 15−22 μmol L −1 for NO 2 − ) in the biochar and biochar + AQDS amendments ( Figure S1). …”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…2,4−6 Several anaerobic pathways contribute to N loss in terrestrial ecosystems, including denitrification, codenitrification, and anaerobic ammonium oxidation (anammox). 2,3 It was recently reported that anammox could be coupled to iron(III) reduction (termed Feammox) with N 2 , NO 2 − , or NO 3 − as the endproducts. 4−7 The following three equations and accompanying free energies summarize these three end routes of Feammox (Δ r G m represents the energy yielded from the balanced redox reaction).…”
Section: ■ Introductionmentioning
confidence: 99%
“…To measure the rates of anammox and denitrification in paddy soils, slurry incubation experiments with 15 NO 3 À were carried out using the protocol as previously described (Long et al, 2013). Briefly, 2 g of soil was added into 12-mL Exetainer tubes (Labco, High Wycombe, UK) and saturated with sterilized distilled water, and the tubes were vacuumed for 1 min and flushed with ultrahigh pure N 2 for 2 min to create anoxic conditions.…”
Section: Slurry Incubation Experiments Withmentioning
confidence: 99%
“…Prevalence of anammox in terrestrial ecosystem such as freshwater wetlands was later reported (Humbert et al, 2010;Zhu et al, 2011a;He et al, 2012). As anammox bacteria are responsible for N loss from farmlands which receive large amount of N fertilizers, studies that focus on anammox in agricultural soils are highly desirable (Long et al, 2013;Shen et al, 2013). Paddy soils are frequently flooded, making these habitats quite similar to freshwater wetlands.…”
Section: Introductionmentioning
confidence: 99%